2016
DOI: 10.1002/clen.201500358
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Sources of Waterborne Viruses in South Sudan Refugee Camps

Abstract: Short Communication Transmission Sources of Waterborne Viruses in South Sudan Refugee CampsOutbreaks of hepatitis E virus (HEV) are typically associated with contaminated drinking water. A recent HEV outbreak in South Sudan affected !10 000 people. This study evaluated different water matrices and food during the last phase of the outbreak by analyzing HEV and human adenovirus (HAdV) as viral indicator of human contamination. The results revealed that the water sources analyzed were negative and that only hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Finally, no positive results were obtained from water samples using the PCR method. One possible reason was that the transmission and circulating period of the viruses may have occurred weeks ago when human cases were infected during the outbreak [38]. On the other hand, detection of water samples was conducted by the local CDC without equipment for water enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, no positive results were obtained from water samples using the PCR method. One possible reason was that the transmission and circulating period of the viruses may have occurred weeks ago when human cases were infected during the outbreak [38]. On the other hand, detection of water samples was conducted by the local CDC without equipment for water enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…Less frequently reported risk factors were waste management (n=2, 2%) (Connolly et al, 2004;Prothero, 1994), limited access to health care (n=2, 2%) (Connolly et al, 2004;Kimbrough et al, 2012) and young age (n=2, 2%) (Desenclos et al, 1988;Mellou et al, 2017). Pregnancy (n=3, 3%) (Cronin et al, 2008;Guerrero-Latorre et al, 2016;Mcgready et al, 2010) and HIV-positive status (n=2, 2%) (Cronin et al, 2008;Kimbrough et al, 2012) were reported as morbidity and mortality risk factors.…”
Section: Exposures Outcomes and Risk Factorsmentioning
confidence: 99%
“…In refugee and internally displaced persons (IDP) settlements, water-users typically do not have drinking water piped to their premises; instead, they collect water from public distribution points (tapstands) which they then transport, store, and use over time in their dwellings. Recontamination of previously safe drinking water during this post-distribution period of collection, transport, and storage is an important factor in waterborne illness outbreaks, having been linked to outbreaks of cholera, hepatitis E, and shigellosis in refugee and IDP settlements in Kenya, Malawi, Sudan, South Sudan, and Uganda [2][3][4][5][6][7][8][9]. To prevent outbreaks in refugee and IDP settlements, drinking water needs to be protected against pathogenic recontamination until the end of the household storage period when the final cup is consumed.…”
Section: Introductionmentioning
confidence: 99%